Penjernihan Minyak Jelantah Menggunakan Campuran Karbon Batang Kentang (Solanum tuberosum L.) dan Bleaching Earth - Dini Hayati Nufuz; Umar Kalmar Nizar (Lembaga Yasin AlSys, 2026)
Used cooking oil is cooking oil that has undergone degradation due to repeated use at high temperatures, thereby producing oxidation, hydrolysis, and polymerization compounds that reduce oil quality and potentially endanger health and the environment. This study aimed to evaluate the effects of variations in the composition of potato stem carbon (Solanum tuberosum L.) and bleaching earth on the quality of used cooking oil and to determine the most effective adsorbent composition. Potato stem carbon was characterized through proximate analysis and then combined with bleaching earth at mass ratios of 75:25, 50:50, and 25:75 to purify used cooking oil. The quality of the purified oil was evaluated based on density, flow rate, acid value, and saponification value. The proximate analysis results showed that potato stem carbon had a moisture content of 10.05%, an ash content of 9.50%, a volatile matter content of 2.40%, and a fixed carbon content of 88.10%. Variations in adsorbent composition affected the physicochemical properties of used cooking oil, with the 50:50 composition demonstrating the best performance based on the lowest density of 0.9353 g/mL, the highest flow rate of 0.3080 mL/s, the lowest acid value of 4.8378 mg KOH/g, and the highest saponification value of 66.1884 mg KOH/g. These findings confirm that the combination of potato stem carbon and bleaching earth at a mass ratio of 1:1 produced the most effective synergistic effect in improving the quality of used cooking oil through the adsorption process and has the potential to be used as an alternative adsorbent for used cooking oil purification.